Evidence of Recombinant Isolates of Potato Virus Y (PVY) in Argentina - Colavita, Monica; Lancia, Marcos; Feingold, Sergio Enrique; Massa, Gabriela Alejandra (Springer Netherlands, 2018)
In order to make a first approach in the identification of the genetic diversity of Potato virus Y (PVY) in Argentina, 46 PVY isolates from different potato growing regions of Argentina were characterized both, biological and serologically. Five of them (ST11, RCA5a, RCA6, RCA14b and SSF6) were selected for further genomic analyses. Four genomic fragments containing hot spot regions of recombination (HSR) reported previously were sequenced in each isolate and compared to PVYN (CS434575.1) and PVYO (U09509.1) reference genomes looking for genomic recombinations. Isolates with one, two or three recombination points were identified among these, including the two strains considered typical PVYN (RCA5b) and PVYO (SSF18) used as controls. This is the first report of the presence of recombined PVY in Argentina using a combination of biological, serological and molecular tools that shed light on the genetic diversity of PVY viruses in this country.